An investigation into set back force simulation in composition B fillings subjected to hot gun scenarios - Cartwright, M.; Delany, P. (Cranfield University, 2008)
Ammunition loaded into large calibre gun chambers, which have been heated by previous firings, can enter a hot-gun state; conservatively defined as hot if 50 rounds or more are fired in a four-hour period. In this state the temperatures of the explosive fill, such as Composition B, may easily exceed their qualification temperatures. This is potentially dangerous if the weapon misfires either by cook-off or premature shell ignition. Currently there are no standard tests that can be used to assess the behaviour of Composition B filled munitions in a simulated hot-gun condition. During firing some of the energy can be transferred to the explosive fill. Defects induced by melting and/or re-solidification of the Composition B will lead to a greater chance of accidental initiation of the explosive due to setback forces creating hotspots and ultimately resulting in an accidental in-bore explosion. The aim of this research was to investigate the conditions of this accidental initiation of Composition B in a hot gun situation at the time the projectile is likely to be cleared from the gun. It investigated whether this situation can be simulated cost effectively by examining the sensitivity of Composition B samples that were thermally conditioned in accordance with calculated temperature-time profiles. A target assembly was designed to mimic setback forces by using projectile impact. A series of tests conducted on these composition B filled targets, which had been subjected to hot gun conditions, were performed at the Cranfield Ordnance Test and Evaluation Centre (COTEC) to simulate setback effects at shot start. Mechanical energy was delivered by an impacting sabot launched from a nitrogen gas powered gun. Post firing simulation and analysis of materials were used to determine the mechanism of initiation and the severity of the event compared to the amount of force the samples were subjected to.
presented at PARARI, Melbourne in November 2007